KONTRASTIF FONEM TUNGGAL BAHASA INDONESIA DAN MANDARIN (Sebuah Studi Analisis Kontrastif Bahasa) - Ekapartiwi, Alexandra Sawitri (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
When learning a foreign language or second language learning (L2) for native language users (L1), there are some differences which learners cannot avoid. Several factors underlie that problem. Chinese learners in Indonesia also experience the problem. Pinyin spelling system is quite different from Indonesian spelling system and it causes some distinctions in L1 and L2. Contrastive Analysis approach (henceforth anakon) can be the answer to solve the problem. A subordinate study by Carl James discusses two main difficulties in phonology and structure. Anakon can be understood by outlining the meaning of L1 and L2 words. By using anakon, the differences between L1 and L2 will get clearer.